(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Now a days, several patients are reporting to the hospitals by regularly affecting with different Mutrabaha Srotas disorders like burning micturation, urinary stone diseases etc. Mutrashmari is one of the important diseases of Mutrabaha Srotas. This may caused due to the intake of adulterated food and polluted water. So, it becomes important to know the details about this disease in terms of Nidana (etiological factors), Samprapti (Pathogenesis), lakshyanas (symptomatology), Upadrava (complications), Sadhya-sadhyata (prognosis) and chikitsa (management) of this disease, in order to treat or prevent the disease. Here an effort was made to describe details about this disease both in Ayurvedic as well as modern view and interpreted each other. It helps physician to know about this disease in detail. So that, they can treat successfully to this disease for the benefits of mankind.